Photoinduced Trap Passivation for Enhanced Photoluminescence in 2D Organic–Inorganic Hybrid Perovskites. Issue 7 (5th February 2020) - Song, Yiling; Liu, Weiwei; Qin, Yan; Han, Xiaobo; Li, Wancai; Li, Xiaohong; Long, Hua; Li, Dehui; Wang, Kai; Wang, Bing; Lu, Peixiang
Abstract: 2D organic–inorganic hybrid perovskites are promising materials for next‐generation optoelectronic devices. Nevertheless, 2D perovskites still suffer from performance‐limiting trap states and possess fundamental photophysical effects that remain poorly understood. Herein, a photoinduced trap passivation for enhanced photoluminescence (PL) in 2D hybrid perovskites is reported. Under two‐photon excitation, the PL emission of the 2D hybrid perovskites exhibits a gradual increase in intensity and lifetime, due to the photoinduced trap passivation by interacting with oxygen in ambient environment. Interestingly, the PL increase shows distinct features at the surface and in the bulk of the 2D perovskites, which can be well revealed by a photoinduced oxygen‐diffused trap‐passivation model. Moreover, the PL increase and relaxation can recycle for several times, which suggests an excellent repeatability of the photoinduced trap passivation. The photoinduced trap passivation is critical for fundamental study of light–matter interaction in 2D perovskites, and shows great promise for improving the optoelectronic responses for functional devices. Abstract : Photoinduced photoluminescence enhancement is demonstrated in 2D hybrid perovskite monocrystalline films under two‐photon excitation, which is correlated to trap passivation in the perovskite. The photoinduced trap passivation exhibits an excellent repeatability and can recycle for several times.